CEO Overconfidence and Ambidextrous Innovation. (August 2017) - Wong, Ying-Jiuan; Lee, Cheng-Yu; Chang, Shao-Chi
While prior research has focused on the effect of CEO overconfidence on innovation, few studies have been conducted to reveal how and whether an overconfident CEO affects ambidextrous innovation, which means the simultaneous and balanced pursuit of both exploratory and exploitative innovation. By observing firms' patenting behavior, we investigate the effect of CEOs' psychological attribute of overconfidence on innovation ambidexterity. In addition, we examine how a firm's governance system moderates the relationship between CEO overconfidence and ambidextrous innovation. The results show that overconfident CEOs are more apt to create or magnify an imbalance in innovation ambidexterity. Furthermore, the results regarding the moderating effects of governance and monitoring mechanisms indicate that an independent board and dedicated institutional ownership mitigate the positive relationship between CEO overconfidence and a firm's ambidextrous imbalance, while transient institutional ownership enhances this relationship. We also find that analyst following does not effectively monitor an overconfident CEO's tendency toward an ambidextrous imbalance.